The Effect of Rentier Economy on the Urban Space Organization with an Emphasis on Malls and Large Business Spaces (Case Study: 1st and 5th Districts of Tehran) - Saeedifard, Faranak; Neda Bagheri,; Shahed, Seyed Hosein; Babai, Akram; Salmanzadeh, Sina; Jaafari, Masoumeh; Sobhani, Nobakht; Ghodsi, Mehrnoush (Technium Social Sciences Journal, 2020)
In the backdrop of a rentier economy, the malls connect the place to the global production network, increase consumerism and rent-seeking through improper locationing. Malls have been described as “urban spaces”,“enterprise-oriented spaces”,“a space for consumerism”,“a physical space for loitering”,“space of the simulacrum”,??”profitable and alien spaces with the structure of a pan option”, and “a new public space”. The metropolitan space of Tehran has become a commodity for the goals of the rentier and speculative economy because of the “disembedded” capitalist system, land rent and density sale combined with construction of malls and real estate bourgeoisie. The manifestations of this rentier economy can be analyzed in the economic, physical, environmental, social, and political-management structures. In this research, Districts 1 and 5 have greatly been affected by the flow and relations of rentier economy, especially the real estate bourgeoisie, and have had the most spatial changes in Tehran metropolis in terms of construction of malls and their locationing. Analytic Hierarchy Process (AHP) was used for SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis. SWOT-AHP model was used to describe the goals and strategies. The final result of the evaluation of internal and external factors indicates that the most important strategies for the organization of urban spaces with the approach of human-oriented cities is to locate malls outside the cities, to reduce land and housing rents, to prevent the locationing of malls based on “land rent”, to protect human-oriented spaces, and to avoid the destruction of local economy through brandism which is promoted by malls.